2019
DOI: 10.1177/2319510x19883089
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Job and Family Satisfaction: Scale Validation and Role of Demographic Variables

Abstract: Satisfaction from job is considered as an important variable for study with respect to sales employees. By virtue of their job profile, sales employees are required to respond to multiple demands from multiple stakeholders both at work and family front which eventually lead to negative outcomes such as stress. This in turn results in lesser satisfaction both in work and family domains. Although job satisfaction gets highlighted across researches (especially in western context), family satisfaction still remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…This clearly indicates that the top management employees, due to greater remuneration, challenging work to be performed, lesser monotony, better communication with superiors, have greater satisfaction as compared to the employees at lower levels. Similar results were found in various studies (Singh & Srivastava, 1975;Saiyadain, 1977;Veronique &Stephen, 2006 andJain &Nair, 2019). The pioneering study proving a positive relationship between management level and job satisfaction comes from Porter (1961) who revealed that "the vertical location of management positions appears to be an important variable in determining the extent to which psychological needs are fulfilled".…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This clearly indicates that the top management employees, due to greater remuneration, challenging work to be performed, lesser monotony, better communication with superiors, have greater satisfaction as compared to the employees at lower levels. Similar results were found in various studies (Singh & Srivastava, 1975;Saiyadain, 1977;Veronique &Stephen, 2006 andJain &Nair, 2019). The pioneering study proving a positive relationship between management level and job satisfaction comes from Porter (1961) who revealed that "the vertical location of management positions appears to be an important variable in determining the extent to which psychological needs are fulfilled".…”
Section: Discussionsupporting
confidence: 83%
“…Some researchers have reported that the relationship between age and employees' level of job satisfaction is 'U' shaped, which means, positive perception about work organization declines from a moderate level in the early years of employment and then increases steadily up to retirement (Clark, Oswald, & Warr, 1996;Warr, 1992). This is in contradiction with some previous studies by (Salami, 2008) and (Jain & Nair, 2019) However, it was also evident that job satisfaction increased with age, with the employees in the 21 to 30 years age category had the least means, it increased in the next category i.e. 31to 40 years, then decreased in 41-50 years and lastly increased in the 51-60 years age category.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Employees with unmarried status have higher job satisfaction than married employees (Sutanto and Anggraini, 2011). Still, there are also studies that state that married employees have a higher level of satisfaction than employees with unmarried status (Jain and Nair, 2019). That is possible because there is a factor in the importance of a job in a person's career, apart from their marital status, which results in employees developing positive feelings about their work by ignoring their negative aspects.…”
Section: Moderating Effects Of Employee Demographicsmentioning
confidence: 99%
“…Family satisfaction scale: Family satisfaction was assessed using Hennessy's ( 2007) modified version of the family satisfaction scale developed by Brayfield and Rothe (1951). This scale was later validated in the Indian context by Jain and Nair (2019). Cronbach's alpha was found to be 0.969 for the family satisfaction scale.…”
Section: Moderating Role Of Demographic Variablesmentioning
confidence: 99%